Good agricultural practices for ware potato production in Cameroon: Visual aid - Harahagazwe, D.; Atieno, E.; Schulte-Geldermann, Elmar; Kromann, P.; Mafouo, H.; Anagho, R.; Schuffenhauer, A.; Sossou, L.; Breitenstein, A.; Festus, K.A. (Deutsche Gesellschaft für Internationale Zusammenarbeit, 2018)
The Trainer Visual Aid is a didactic tool which helps the trainer to train participants. It includes four components for each of the 18 modules (figures): (i) a small format of the front page image; (ii) a brief summary of the theory in bullet points in which keywords are provided in bold, (iii) three guiding questions, and (iv) a take home message.